USING VIDEO BASED COMPUTER MEDIATED COMMUNICATION IN TEACHING READING - Harsanto, Ghossan Fa'iq; Al Hakim, Luqman (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The use of computer/ laptop as a medium of communication is a necessity to fulfill the needs of learning during pandemic to attain learning objectives. The present article aims at showing the implementation of teaching reading though computer mediated communication (CMC), particularly in using video as learning medium to assist students in understanding English text well and to interact in group actively in online learning. The subject of research is 2nd semester students class 01 who are 17 students. The type of research is classroom action research. The methods of collecting data are observation and a questionnaire. In analyzing the data, the researchers used interactive analysis that comprises data display, data reduction, and drawing conclusion. Research findings show that the use of video in CMC assists the students to understand the text being learnt properly and they interacted with their friends to discuss the materials of learning and assignments. The conclusion of the present article is that the use of video in CMC is a solution of learning in the pandemic situation to give visualization of the text being learnt. Keywords: computer mediated communication, teaching reading